Penerapan bimbingan kelompok dengan teknik konseling individual untuk meningkatkan disiplin belajar siswa SMK Negeri 5 Mataram - Gustijati Hortensi (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
The research conducted was classroom action research. This study aims to determine the effectiveness of individual counseling as an effort to improve the discipline of class X DKV-A students in second semester SMKN Mataram 5 in the academic year 2019/2020 on school discipline. The subjects of the research were students of class X DKV-A in second semester SMKN Mataram 5 in the academic year 2019/2020. The object of research is student discipline following school rules.Student discipline data on school rules were collected using an observation format and analyzed descriptively qualitatively. The success criteria determined are as follows: 1) the average score of student discipline on the minimum school discipline in the category is rather good, (2) the percentage of student discipline that reaches the minimum category is rather good more than 80%.After conducting an action research, there was an increase in the results of preliminary data (prasiklus), the average score of discipline was 61.57, with the percentage of students whoachieved discipline in the minimal category quite good at 22.85%; increased in the first cycle with an average score of student discipline reaching 72.43 and the percentage of students achieving discipline in the minimal category was quite good at 74.29%; and in the second cycle increased the average score of students discipline to 82.48 and the percentage of students who achieved discipline in the minimal category was quite good at 94.29%. In conclusion, the use of individualtutoring techniques can improve the discipline of class X DKV-A students in Second Semester of SMKN 5 Mataram in the 2019/2020 Academic Year following school discipline has been successful in two cycles. Jenis penelitian yang dilakukan adalah penelitian tindakan kelas.Penelitian ini bertujuan untuk mengetahui efektivitas konseling individual sebagai upaya untuk meningkatkan kedisiplinan siswa kelas X DKV-A Semester II SMKN 5 Mataram Tahun Pelajaran 2019/2020 dalam mengikuti tata tertib sekolah. Subjek penelitiannya adalah siswa kelas X DKV-A semester II SMKN 5 Mataram tahun pelajaran 2019/2020. Objek penelitian adalah kedisiplinan siswa mengikuti tata tertib sekolah. Data kedisiplinan siswa untuk mengikuti tata tertib sekolahdikumpulkan menggunakan lembar observasi dan dianalisis secara deskriptif kualitatif. Kriteria keberhasilan yang ditentukan adalah sebagai berikut: (1) nilai rata-rata kedisiplinan siswa mengikuti tata tertib sekolah minimal dalam kategori cukup baik, (2) persentase kedisplinan siswa yang mencapai kategori minimal cukup baik lebih dari 80%. Setelah dilakukan penelitian tindakan terjadi peningkatan hasil dari data awal (prasiklus) yang semula nilai rata-ratakedisiplinan 61,57 dengan persentase siswa yang mencapaikedisiplinan kategori minimal cukupbaik sebesar 22,85%; meningkat pada siklus I dengan nilai rata-rata kedisiplinan siswa mencapai72,43 dan persentase siswa yang mencapai kedisiplinan kategori minimal cukup baik sebesar74,29%; dan pada siklus II meningkat lagi nilai rata-rata kedisplinan siswa mencapai 82,48dan persentase siswa yang mencapai kedisiplinan kategori minimal cukup baiksebesar94,29%. Kesimpulan,penggunaan teknik konseling individual sebagai upaya untuk meningkatkan kedisiplinan siswa kelas X DKV-A Semester II SMKN 5 Mataram Tahun Pelajaran 2019/2020 mengikuti tata tertib sekolah telah berhasil dalam dua siklus.